Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0544
|View full text |Cite
|
Sign up to set email alerts
|

MitochondrialDNARepair and Genome Evolution

Abstract: In plants, replicating the mitochondrial genome is probably a very minor expenditure of energy compared to the other costly activities of the cell, including replicating the much larger nuclear genome, transcription, protein synthesis and active transport. This chapter discusses the angiosperm mitochondrial genomes. The mutational burden hypothesis (MBH) explains an inverse correlation between mutation rate and genome size. The types of DNA damage that occur in mitochondria, the available mechanisms of repair,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 95 publications
2
38
0
Order By: Relevance
“…The underlying processes generating this heterogeneity are largely unclear: for each mitogenome supporting a given mechanistic hypothesis, another often suggests the opposite, such as in the relationship between mutation rate and genome size (cf. Sloan et al 2012; Skippington et al 2015, Christensen 2018). The P. abies mitogenome and our comparative analyses may lend support to the view of plant mitogenomes as highly idiosyncratic and driven mainly by rapid evolution and/or considerable genetic drift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying processes generating this heterogeneity are largely unclear: for each mitogenome supporting a given mechanistic hypothesis, another often suggests the opposite, such as in the relationship between mutation rate and genome size (cf. Sloan et al 2012; Skippington et al 2015, Christensen 2018). The P. abies mitogenome and our comparative analyses may lend support to the view of plant mitogenomes as highly idiosyncratic and driven mainly by rapid evolution and/or considerable genetic drift.…”
Section: Resultsmentioning
confidence: 99%
“…Recombination rates vary extensively among plants and small repeats (< 1,000 bp) are highly active in a third of the reported species. Recombination affects the accumulation of mutations (Maréchal & Brisson 2010; Christensen 2018), influences genome size (Christensen 2018), and induces structural rearrangements (Palmer & Herbon 1988), making this variation a potential but understudied contributor to the diversity of plant mitogenomes.…”
Section: Resultsmentioning
confidence: 99%
“…Both DNA polymerases found in A. thaliana mitochondria, POL1A and POL1B, exhibit 5 -dRP lyase activity, allowing them to remove the 5 dRP and to polymerize a new nucleotide replacing the uracil [48]. In the absence of functional UNG protein, cytosine will still be deaminated in plant mitochondrial genomes, so efficient removal of uracil must be through a different repair mechanism, most likely DSBR [14,15]. We have found that, in UNG mutant lines, there is an increase in the expression of genes known to be involved in DSBR and significant changes in the relative abundance of parental and recombinant forms of intermediate repeats, consistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is no evidence of nucleotide excision repair (NER) or mismatch repair (MMR) in plant mitochondria [12,13]. It has been hypothesized that, in plant mitochondria, the types of DNA damage that are usually repaired through NER and MMR are repaired through double-strand break repair (DSBR) [14,15]. Plant mitochondria do have the nuclear-encoded base excision repair (BER) pathway enzyme Uracil DNA glycosylase (UNG) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation